Development of arrayed microcolumns and field emitters. (17th May 2017) - Kim, Ho Seob; Lee, Young Bok; Choi, Sung Woong; Kim, Hyung Woo; Kim, Dae-Wook; Ahn, Seung Joon; Oh, Tae Sik; Song, Yoon-Ho; Park, Byong Chon; Lim, Sun Jong
Abstract: Electron beam devices have been widely used for inspection or lithography processes. The multibeam technology based on arrayed microcolumns has been developed to overcome the low throughput issue. However, the multicolumn system has some drawbacks such as complexity, electron optics, and electron source. The first drawback is the difficulty in multicolumn assembly. In particular, the alignment process of a source lens and a tip requires sophisticated techniques. The second drawback is that the e-beam characteristics of microcolumns constituting the multicolumn differ from column to column. To solve the first drawback, a sub-5-nm-resolution probe beam optic design with a simple structure and a two-dimensional carbon nanotube (2D-CNT) electron emitter instead of the widely used tungsten field emitter tip have been studied.